2012
DOI: 10.1371/journal.pone.0031472
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Displaying Lipid-Enveloped PLGA Nanoparticles as Delivery Agents for a Plasmodium vivax Malaria Vaccine

Abstract: The parasite Plasmodium vivax is the most frequent cause of malaria outside of sub-Saharan Africa, but efforts to develop viable vaccines against P. vivax so far have been inadequate. We recently developed pathogen-mimicking polymeric vaccine nanoparticles composed of the FDA-approved biodegradable polymer poly(lactide-co-glycolide) acid (PLGA) “enveloped” by a lipid membrane. In this study, we sought to determine whether this vaccine delivery platform could be applied to enhance the immune response against P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 35 publications
1
106
0
Order By: Relevance
“…Cell viability was expressed as a percentage based on control (untreated) cells. Additionally, CCK-8 assays were performed with HEK293 cells for groups with different concentrations (15,30,60, and 90 µg).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…Cell viability was expressed as a percentage based on control (untreated) cells. Additionally, CCK-8 assays were performed with HEK293 cells for groups with different concentrations (15,30,60, and 90 µg).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…DLS analysis revealed that there was a significant size reduction (Figures 2A, S1) compared to bare PLGA NSs (247±12.8 nm), which could be explained by the fact that the processing of those particles in a single step was stabilized by the function of the lipids with PVA. 15,20 It was also found that there was a decrease in particle size Notes: LPHNSs that consisted of DOTAP-protamine-PLGA for efficient gene delivery were fabricated by emulsion-solvent evaporation with a self-assembly process.…”
Section: Influence Of Cationic Lipid Concentration On Size and Size Dmentioning
confidence: 99%
See 2 more Smart Citations
“…7 PLGA-based vaccine delivery systems possess several advantages such as sustained and controlled antigen release, adjuvant co-encapsulation, protection from degradation by enzymes, as well as the ability of specific tissue targeting. 8,9 Several studies have demonstrated that these nano-sized delivery systems can induce both humoral and cell-mediated specific immune responses via activation of dendritic cells (DCs) in animals in combination with tumor antigenic peptides, 10,11 or parasitic 12 or viral antigenic molecules. 13,14 Several types of micro-or nanoformulations (ie, liposomes, chitosan, PLGA) and antigens have been tested up till now for vaccine development against leishmaniasis with encouraging results.…”
Section: Introductionmentioning
confidence: 99%